2021
DOI: 10.3390/idr13040084
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Booster: To Boost or Not to Boost

Abstract: Developing safe and effective vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at a breakneck speed has been an exceptional human achievement. It remains our best hope of containing the coronavirus disease 2019 (COVID-19) pandemic. However, newer, more aggressive SARS-CoV-2 viral strains, as well as the possibility of fading immunity following vaccination, have prompted health officials to investigate the necessity for additional immunization. This has put further pressure on disre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 25 publications
(31 reference statements)
2
85
0
2
Order By: Relevance
“… 1 , 2 , 3 However, the effectiveness against infection, as happens also for other vaccines, wanes within months of the second dose. 4 , 5 Studies in Qatar showed substantial waning 6 , 7 in effectiveness against SARS-CoV-2 infection from month 4 after the second dose for BNT162b2 (tozinameran; Pfizer-BioNtech), 6 , 7 although effectiveness against severe disease, hospitalisation, and death remained high 6 months after vaccination for both BNT162b2 and mRNA-1273 (elasomeran; Moderna). 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 However, the effectiveness against infection, as happens also for other vaccines, wanes within months of the second dose. 4 , 5 Studies in Qatar showed substantial waning 6 , 7 in effectiveness against SARS-CoV-2 infection from month 4 after the second dose for BNT162b2 (tozinameran; Pfizer-BioNtech), 6 , 7 although effectiveness against severe disease, hospitalisation, and death remained high 6 months after vaccination for both BNT162b2 and mRNA-1273 (elasomeran; Moderna). 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that six months after the administration of the second dose of the BNT162b2 vaccine, the humoral response was substantially reduced [8]. The Centers for Disease Control and Prevention has recommended a third COVID-19 vaccine dose in immunocompromised individuals [9]. As described above, reducing the number of unvaccinated individuals and minimizing vaccine hesitancy to facilitate more people receiving a third dose, is an extremely important measure in controlling the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A booster dose was received by 18.5% of the subjects. Governments and health care officials should optimize the usage guidelines for COVID-19 vaccine booster doses in view of the potential waning immunity and emerging viral strains and should prioritize populations at risk in lower-income countries [ 32 ]. In a nationwide Italian study on the COVID-19 vaccine, primary vaccination efficacy was 76–92% within 6 months that decreased to 34–80% thereafter.…”
Section: Discussionmentioning
confidence: 99%